KONSEP KEDAULATAN RAKYAT DALAM PRAKTIK KETATANEGARAAN MODERN - Thaher, Irmanjaya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The concept of popular sovereignty is a fundamental pillar of modern democratic governance systems, encompassing theoretical, normative, and empirical dimensions. This research examines the philosophical foundations, institutional mechanisms, and practices of public participation in the implementation of popular sovereignty.The research objective is to comprehensively analyze the concept of popular sovereignty through a synthesis of theoretical perspectives, exploring institutional mechanisms, analyzing the role of public participation, identifying implementation challenges, and formulating implications for strengthening popular sovereignty in modern governance.The research employed a Systematic Literature Review (SLR) method, conducted systematically, structured, and transparently to identify, evaluate, and synthesize relevant scholarly articles.The results show that popular sovereignty has a strong philosophical foundation derived from the classical thinking of Locke and Rousseau, which remains relevant in modern constitutionalism. Implementation through a representative system faces significant challenges in balancing democratic ideals with government effectiveness, requiring a strengthened legal framework and comprehensive institutional reforms to ensure government accountability and responsiveness.Meaningful public participation is a substantive manifestation of popular sovereignty that is essential in the policy cycle, but faces structural obstacles such as corruption and social injustice. There is an inherent tension between the aspirations of popular sovereignty and its practice that can trigger populist responses, so a balance is needed between democratic aspirations and the constitutional framework to prevent the tyranny of the majority and protect the rule of law.